2017
DOI: 10.5751/es-09249-220216
|View full text |Cite
|
Sign up to set email alerts
|

Landscape and biodiversity as new resources for agro-ecology? Insights from farmers’ perspectives

Abstract: ABSTRACT. Pesticide reduction is a key current challenge. Scientific findings in landscape ecology suggest that complex landscapes favor insect pest biological control by conservation of natural enemy habitats. A potential agro-ecological innovation is to conserve or engineer such complex landscapes to reduce pesticide use. However, whereas the relevant resources are often well known in most natural resource management situations, potential resources involved in this innovation (natural enemies and the landsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 23 publications
0
27
0
3
Order By: Relevance
“…Em contraponto, todavia, Salliou e Barnaud (2017) afirmam que a incredulidade dos agricultores quanto à eficiência do controle biológico em substituição aos pesticidas químicos, ou seja, a falta de confiança pública na biotecnologia (MCCARTHY; LIU; CHEN, 2016) tende a dificultar o desenvolvimento de ecoinovações de produto (BLAZY et al, 2010;SALLIOU;BARNAUD, 2017). Por conseguinte, emerge a criação de cadeias de valor mediante a integração de distintos modelos de negócio, como o turismo agroalimentar (LIU et al, 2017) ou turismo rural em paralelo à exploração de pecuária orgânica (GENOVESE et al, 2017).…”
Section: Abordagens Da Ecoinovação No Contexto Agrícola/agronegocialunclassified
See 1 more Smart Citation
“…Em contraponto, todavia, Salliou e Barnaud (2017) afirmam que a incredulidade dos agricultores quanto à eficiência do controle biológico em substituição aos pesticidas químicos, ou seja, a falta de confiança pública na biotecnologia (MCCARTHY; LIU; CHEN, 2016) tende a dificultar o desenvolvimento de ecoinovações de produto (BLAZY et al, 2010;SALLIOU;BARNAUD, 2017). Por conseguinte, emerge a criação de cadeias de valor mediante a integração de distintos modelos de negócio, como o turismo agroalimentar (LIU et al, 2017) ou turismo rural em paralelo à exploração de pecuária orgânica (GENOVESE et al, 2017).…”
Section: Abordagens Da Ecoinovação No Contexto Agrícola/agronegocialunclassified
“…Um dos principais desafios da difusão da inovação é a relação entre a eficiência de produtos ecoinovadores e os impactos ambientais, haja vista a incredulidade da eficácia do controle biológico em comparação ao químico, por exemplo (JONGE, 2004;LEACH et al, 2012;SALLIOU;BARNAUD, 2017), ou ainda o trade-off entre perdas de produção e impacto econômico (SAINT-GES; BÉLIS BERGOUIGNAN, 2009). Assim, fatores ideacionais (como o impacto percebido por uma tecnologia na rentabilidade), fatores institucionais (a exemplo da promoção de métodos específicos) ou fatores logísticos (como a facilidade de instalação e manutenção da tecnologia oferecida) podem explicar as causas que tornam uma ecoinovação ser difundida em maior escala do que outras MARIOLA;HANSEN, 2008).…”
Section: Tendências E Desafios Da Ecoinovação No Contexto Agrícola/agunclassified
“…A first success in the use of natural enemies to regulate pests was achieved against the European red mite (Panonychus ulmi) on apple trees. The integration of Aphelinus mali, which parasitizes woolly aphids (Eriosoma lanigerum), and the introduction of Neodryinus typhlocibae against Metcalfa pruinosa invasive pests are some notable later successes [35]. While further advances in integrated pest management have been achieved, pesticide use remains by far the main pest control option in the area, which reflects the general situation in France.…”
Section: Case Studymentioning
confidence: 99%
“…It was found that, in most natural resource management situations, potential agroecological means considering the importance of the complexity of landscape and the natural enemies to control plagues and reduce the use of pesticides, are not necessarily considered as resources for their potential users (agricultural producers), since in some cases they were perceived more as a source of pests [62]. In this sense, for the European context, it has been recommended to implement agroforestry strategies as key elements for agriculture and food security to optimize sustainable intensification and balance the competitive demands over land for the production of food and energy.…”
Section: Agroecology As Agricultural Practice In Biodiversity and Lanmentioning
confidence: 99%
“…In front of these results, the scientific findings, for example of landscape ecology, suggested that complex landscapes favor the biological control of insect pests by conserving the habitats of their natural enemies [62]. Faced with the fact of confronting modern societies, some authors mentioned that farmers should not only be efficient in food production, but also ensure that ecological services (pollination, pest control or conservation of biodiversity) are effective, which raises the need to reconsider the role of the environment by redesigning or evaluating the agricultural systems [78].…”
Section: Physical-biological Factorsmentioning
confidence: 99%